Rhetorical Techniques in Debates and Their Effectiveness - Nilufar Babajonova; Salimova Kumushxon Talat qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This paper explores the rhetorical techniques used in debates and their effectiveness in influencing audiences. It examines key elements of public speaking, such as logical argumentation, emotional appeal, persuasive speech structure, and body language. The study analyzes how debaters utilize these techniques to strengthen their positions and how these strategies psychologically affect listeners. The findings highlight that oratory skills are essential for achieving success in competitive debates.